PENGAPLIKASIAN METODE EARNED VALUE PADA PENGENDALIAN WAKTU TERHADAP BIAYA (Study Kasus: Proyek Penggantian Jembatan Sungai Langkolome Cs Kabupaten Muna) - Meitri Laura Bulo; Rudi Balaka; Rini Sriyani (STABILITA || Jurnal Ilmiah Teknik Sipil, 2013)
AbstractControl is one of the functions of project management that aims to make the jobs can run reach the target without much deviation. The concept of Value Results (eraned Value) is a control method that is used to control project costs and schedules in an integrated manner. The study "Application of Earned Value Method in Control Against Time Costs (Case Study)" held for 3 months to finish by means of collecting data - the data that is required. In this case, the data work on the project, monthly reports, weekly reports, Schedule implementation, RAB, unit price, and others - others. River Bridge Replacement Project Langkolome Cs located in Muna, District of South Wakorumba, Wambona Village, Southeast Sulawesi has a contract value of Rp. 5,279,117,000.00 to the project implementation time of 180 calendar days. Information obtained on reporting until in June is Budgeted Cost forWork Schedule (BCWS) = USD $ 688,842,961.11, Budgeted Cost For Work Performed (BCWP) = Rp. 1,016,985,385.83 and Actual Cost For Performed (ACWP) = Rp. 891,109,957.50. At this time the better the performance of the project from planning, in the sense of spending less than budget. Performed Cost Index (CPI) = 1.14 > 1 and Schedule Performance Index (SPI) = 1.47 > 1, shows the execution of the work ahead of schedule planned work.Keywords: Cost of Work Scheduled, Work performed Budget, Actual Cost for Work Performed.